Capitalising on chaos – exploring the impact and future of social media influencer engagement during the early stages of a global pandemic - Archer, Catherine (Media International Australia, 2021)
This article examines the role of influencers during the early stages of the COVID-19 pandemic, as well as the impact of the global pandemic on Social Media Influencers’ (SMIs) lifestyle and business model, using the concept of Disaster Capitalism as a springboard for discussion. Worldwide it first appeared that the global pandemic would severely impact SMI sole traders, as income from travel, luxury goods and other ‘lifestyle’ brands dried up. However, we suggest that brands and influencers themselves have pivoted to meet the COVID challenge, with some brands exploiting the opaque influence of these micro-celebrities. We further suggest that while a handful of governments and health organisations have recognised the reach and social capital of SMIs, their potential in health communication has been underutilised. We write this essay as a starting point, raising questions and calling for further research to be conducted to inform the understanding of SMIs’ role and potential as conveyors of public health information.